2014
DOI: 10.1183/09031936.00203613
|View full text |Cite
|
Sign up to set email alerts
|

High risk and rapid appearance of multidrug resistance during tuberculosis treatment in Moldova

Abstract: Multidrug-resistant tuberculosis (MDR-TB) is a serious problem in the former Soviet Union and may appear during TB treatment. We aimed to estimate the prevalence of, timing of and factors associated with MDR-TB diagnosis during TB treatment in Moldova, which was part of the former Soviet Union. We analysed data on 3 754 confirmed non-MDR-TB cases (between January 1, 2007 and December 31, 2010) in the Moldovan TB surveillance database, where patients provided sputum specimens for drug-susceptibility testing, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Our model does not take into account nosocomial transmission of MDR/RR-TB. While we acknowledge this as a possible cause of MDR/RR-TB presentation at re-treatment [33, 34], insufficient data were available to inform its isolated contribution at the local level. Nevertheless, we can anticipate that our model may underestimate the contribution of reinfection in settings where nosocomial transmission of MDR/RR-TB is significant.…”
Section: Discussionmentioning
confidence: 99%
“…Our model does not take into account nosocomial transmission of MDR/RR-TB. While we acknowledge this as a possible cause of MDR/RR-TB presentation at re-treatment [33, 34], insufficient data were available to inform its isolated contribution at the local level. Nevertheless, we can anticipate that our model may underestimate the contribution of reinfection in settings where nosocomial transmission of MDR/RR-TB is significant.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in Moldova found that communities with a larger proportion of previously incarcerated patients with tuberculosis were more likely to be MDR hotspots than communities with fewer of these patients. 29 Similarly, using county-level data from China, another group showed that factors such as health resources, health services, tuberculosis treat ment, and tuberculosis detection, but not socioeconomic status, were associated with drug resistance. 30 …”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…Further analysis revealed that drug-resistant patients tended towards unfavorable prognosis compared with drug-susceptible patients. Drug-resistant TB, particularly MDR-TB, was associated with long-term and complicated treatment, poor prognosis, and severe sequels, 17 18 , 29 in addition to imposing a tremendous emotional burden on patients and medical workers. 30 Therefore, clinicians should consider the possible diagnosis of drug-resistant TB when UTB patients complain of heavier, retreated disease or delayed healing.…”
Section: Discussionmentioning
confidence: 99%